Industrial, mechanical and manufacturing science - Zheng, Dawei (Computer scientist) (IRAICS proceedings series, 2015)
This proceedings volume contains selected papers presented at the 2014 International Conference on Industrial, Mechanical and Manufacturing Science, held in Tianjin, China. Contributions cover the latest developments and advances in the field of Industrial, Mechanical and Manufacturing Science